Effects of Bacillus velezensis FKM10 for Promoting the Growth of Malus hupehensis Rehd. and Inhibiting Fusarium verticillioides - Wang, Chengqiang; Zhao, Dongying; Qi, Guozhen; Mao, Zhiquan; Hu, Xiuna; Du, Binghai; Liu, Kai; Ding, Yanqin (Frontiers in Microbiology, 2020)
Abstract: Bacillus velezensis is a novel species of Bacillus that has been widely investigated and used because of its direct or indirect growth improvement effect for many plants. B. velezensis FKM10 was previously isolated from rhizosphere soil of apple trees and shows potential as a plant growth-promoting and biocontrol bacterium. In this study, strain FKM10 was verified to inhibit some fungal pathogens of soil-borne plant diseases, produce siderophores to absorb ferric iron for plants, and degrade proteins. Pot experiments showed that application of strain FKM10 could directly promote the growth of Malus hupehensis Rehd. by increasing biomass, promoting the absorption of nutrients, improving soil fertility, changing the soil microbial community structure, and reducing fungal diversity. The results of this study provided a basis for using strain FKM10 to improve crop yield and overcome diseases of plants. The mechanism of strain FKM10 to control the phytopathogenic fungus Fusarium verticillioides was studied by interoperation with RNA sequencing. Strain FKM10 can destroy the cell wall and cell membrane of F. verticillioides. The secretion of glucosidases, such as β-glucanase, might be one of the causes of the destruction of the fungal cell wall. The regulation of amino acid metabolism might also play an important role in the antibacterial process of strain FKM10. During the antibacterial process, strain FKM10 attacks F. verticillioides and strain FKM10 itself is also affected: the expression of spores is increased, the number of viable cells is decreased, and the ribonucleoprotein complex and flagellar assembly related genes are downregulated. The results of this study indicate that both strain FKM10 and F. verticillioides have mutually inhibitory activities in a liquid environment. Comparative genome analysis of B. velezensis FKM10 reveals that the general features of their genomes are similar overall and contain the core genome for this species. The results of this study further reveal that B. velezensis can also serve as a basis for developing new biocontrol agents or microbial fertilizers.